Pengaruh beberapa variable terhadap Pemilihan Metode Penilaian Persediaan pada Perusahaan Manufaktur - Herlin Tundjung Setijaningsih; Cecilia Dewi Pratiwi (The Winners, 2009)
This study aims to provide empirical evidence whether the size of the company, inventory intensity, variability cost of sales, and accounting earnings variability influence the choice of inventory valuation methods. The object of this research was manufacturing companies listed in Indonesia Stock Exchange in the period 2005-2009. Thirty nine samples in this study were taken by several criteria. Statistical analysis tool used in this research was logistic regression with a significance level of 5%. From the test result, it was obtained that either partially or simultaneously, company size, intensity of inventory, price variability of goods sold, and income variability have a significance level above 5%. This shows that these variables did not significantly influence the selection method of inventory valuation.